Reference Raman spectra of synthesized CaCl2 · nH2O solids (n = 0, 2, 4, 6). (9th June 2015) - Uriarte, Lucas M.; Dubessy, Jean; Boulet, Pascal; Baonza, Valentin G.; Bihannic, Isabelle; Robert, Pascal; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> The CaCl2 · nH2O solids with n = 0, 1, 2, 4, 6 are of importance in fluid geochemistry in both the Earth and Mars. Their unambiguous identification is thus essential. Raman spectroscopy either in laboratory or in the robotic planet exploration with Raman spectrometer may provide such identification. Published Raman spectra of these minerals were from either unknown, or poorly known or simply wrong samples. The aim of this work is to provide Raman spectra over the 100–4000 cm−1 spectral range for these solids synthesized in capillary and unambiguously identified by X‐ray diffraction. Raman spectra were collected at room temperature and at −172 °C. First interpretations of the Raman spectra of the OH stretching and bending modes of water and of the low‐wavenumber bands (100–1000 cm−1) are given according to the knowledge of their structure. The main Raman bands are given for their identification and will be helpful for ExoMars surface exploration in the next ESA‐Exomars mission in 2016–2018. Copyright © 2015 John Wiley & Sons, Ltd.